Unclear situational models for training of operators of ergatic control systems - Гузий H. H. (Proceedings of National Aviation University (archive), 1998)
Questions of use of unclear situational models for training of operators of ergatic control systems are discussed. Structure imitation and situational functional training-tool of skills of making the decisions along with use of fuzzy models of evaluation of actions of the operator are offered